SIPANDU: An IoT-Based Integrated River Waste Monitoring and Collection System Powered by Solar Energy - Irfan Kamil; Christiono Christiono; Davina Salmah An’nafri; Billy Billy; Surya Lisdi Pamungkas; Yongky Wijaya Hidayat (International Journal of Engineering Continuity, 2026)
River pollution caused by waste accumulation, especially plastic waste, has become a significant environmental problem in urban areas. Rivers act as transportation routes that carry waste from land to sea and contribute to global plastic pollution. Various Internet of Things (IoT)-based water quality monitoring systems have been developed to monitor environmental conditions in real time. However, most existing research still focuses on monitoring environmental parameters without integrating with automatic waste transport mechanisms or independent energy sources, which limits the effectiveness of the system, especially in river locations far from electricity sources. This study proposes SIPANDU (Integrated River Waste Monitoring System), an IoT-based system that integrates direct river condition monitoring, waste transport mechanisms using automatic conveyors, and the use of renewable energy through solar power plants. This system consists of a 100 Wp solar panel, a battery for energy storage, water quality sensors (pH and TDS), an ultrasonic sensor to detect the presence of waste, and a web-based monitoring platform for real-time data visualization. The test results show that the solar panels produce a maximum power of 61.1 W with an average power of around 41.87 W. The conveyor system is capable of transporting up to 5 kg of waste with an average power consumption of 33.43 W. The integration of the IoT system, renewable energy, and automatic waste transportation shows that SIPANDU can function as a river monitoring system as well as a sustainable technology solution for waste management in rivers.